PENGGUNAAN ALAT SENSOR WARNA UNTUK MENDUGA DERAJAT DOMINANSI GEN PENYANDI KARAKTER WARNA BUAH CABAI HASIL PERSILANGAN - Tantri Swandari; Panjisakti Basunanda; Aziz Purwantoro (Program Studi Agroteknologi INSTIPER, 2017)
Colour is an interesting character to be studied in breeding program of ornamental chilli. Colour of plant was affected by the accumulation chlorophyll, carotenoids and anthocyanins that regulated by multiple genes controlling color (gene B, gene cl, gene y + , gene c1 / c2, and gene A). Genes regulating of colour have different dominance degrees thus affecting potential properties inherited in plants. Aim of the research was to determine the alleged dominance of the gene encoding a colour using the colour ratio of female and male parent, and also population of F1 generation. Research materials used are F1 generation and reciprocal accession (A, BR, and CP). The measured parameter was the character of fruit colour using a colour sensor Conica Minotla 400 to get the value of L*a*b* (L: brightness; a: axis extends from green (-a) to red (+a); b: the b axis from blue (- b) to yellow color).Quantitative measurement based on the coordinates L*a* b* showed Chroma and Hue values that describe the color of the fruit. The results showed that the potential value of color brightness ratio of generation F1 and F1R (F1: AxBR, F1R: BRxA) were over dominant. Gene partially dominant shown in cross breeding of accession A and CP (F1: AxCP, F1R: CPxA).